Treatment of resectable gastric cancer - Dikken, Johan L. (SAGE Publications, 2012)
Stomach cancer is one of the most common cancers worldwide, despite its declining overall incidence. Although there are differences in incidence, etiology and pathological factors, most studies do not separately analyze cardia and noncardia gastric cancer. Surgery is the only potentially curative treatment for advanced, resectable gastric cancer, but locoregional relapse rate is high with a consequently poor prognosis. To improve survival, several preoperative and postoperative treatment strategies have been investigated. Whereas perioperative chemotherapy and postoperative chemoradiation (CRT) are considered standard therapy in the Western world, in Asia postoperative monochemotherapy with S-1 is often used. Several other therapeutic options, although generally not accepted as standard treatment, are postoperative combination chemotherapy, hyperthermic intraperitoneal chemotherapy and preoperative radiotherapy and CRT. Postoperative combination chemotherapy does show a statistically significant but clinically equivocal survival advantage in several meta-analyses. Hyperthermic intraperitoneal chemotherapy is mainly performed in Asia and is associated with a higher postoperative complication rate. Based on the currently available data, the use of postoperative radiotherapy alone and the use of intraoperative radiotherapy should not be advised in the treatment of resectable gastric cancer. Western randomized trials on gastric cancer are often hampered by slow or incomplete accrual. Reduction of toxicity for preoperative and especially postoperative treatment is essential for the ongoing improvement of gastric cancer care.